A closed loop supply chain game between a supplier and a manufacturer in a two-stage scenario. Issue 4 (2016) - Bhattacharya, Rabindranath
Tier-I supplier after collection transfers a portion of external return to their supplier in a reverse supply chain in this paper. Supplier derives benefit out of refurbishing of returns. Three scenarios - centralised, decentralised and cooperative - were considered for a two-stage model. Nonlinear unconstrained maximising profitability equations, with normally distributed acquisition prices and deterministic demand were formulated. Solving these for first two models indicated the extent of drop in profit of a decentralised model compared to centralised model. Analysis of cooperative model, based on the results achieved, helps find optimal bounds of transfer and acquisition prices. If both members operate within zone of cooperation, each member earns more profit compared to that in decentralised scenario and overall profit equals centralised one. Study highlights on the decision regarding acquisition price charged by manufacturer for return and transfer price charged by supplier for new product. Decision can be viewed as a contract to arrive at a win-win situation.